2019
DOI: 10.1111/1365-2656.13057
|View full text |Cite
|
Sign up to set email alerts
|

Interaction modifications lead to greater robustness than pairwise non‐trophic effects in food webs

Abstract: Considerable emphasis has been placed recently on the importance of incorporating non‐trophic effects into our understanding of ecological networks. Interaction modifications are well‐established as generating strong non‐trophic impacts by modulating the strength of interspecific interactions.For simplicity and comparison with direct interactions within a network context, the consequences of interaction modifications have often been described as direct pairwise interactions. The consequences of this assumption… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 73 publications
0
19
0
Order By: Relevance
“…This would allow us to recognise fundamental mechanisms involving nontrophic interaction modulation that, for instance, allow the community as a whole to respond to a specific manipulation such as the removal of a species. Advancing our understanding of such mechanisms is likely to elucidate the underlying causes of stability and persistence of ecological communities (Hammill et al 2015;Kelsic et al 2015;Bairey et al 2016;Grilli et al 2017;Terry et al 2019;Singh & Baruah 2021) and increase our ability to predict how they might respond to perturbations. Computational simulations that account for HOIs are helpful, but the results presented here suggest that empirical data will be key to our understanding because of the numerous and often unpredictable opportunities for indirect effects via a variety of mechanisms and pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This would allow us to recognise fundamental mechanisms involving nontrophic interaction modulation that, for instance, allow the community as a whole to respond to a specific manipulation such as the removal of a species. Advancing our understanding of such mechanisms is likely to elucidate the underlying causes of stability and persistence of ecological communities (Hammill et al 2015;Kelsic et al 2015;Bairey et al 2016;Grilli et al 2017;Terry et al 2019;Singh & Baruah 2021) and increase our ability to predict how they might respond to perturbations. Computational simulations that account for HOIs are helpful, but the results presented here suggest that empirical data will be key to our understanding because of the numerous and often unpredictable opportunities for indirect effects via a variety of mechanisms and pathways.…”
Section: Discussionmentioning
confidence: 99%
“…However, HOIs cannot be observed from studying traditional pairwise networks, unlike other indirect effects (e.g., apparent competition) (Morris et al 2004), because they often involve several other species or environmental factors beyond the interacting pair. The role of HOIs in shaping ecological communities has mostly been explored theoretically (Bairey et al 2016;Grilli et al 2017;Mayfield & Stouffer 2017;Terry et al 2019;Singh & Baruah 2021;Kleinhesselink et al 2022) or by experiments with particular subsets of communities and tractable laboratory model systems testing specific effects (Hammill et al 2015;Kelsic et al 2015;Barbosa et al 2019). How pervasive and influential these effects are at a community level, remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Reviews and empirical studies suggest that, by initiating the phenotypic response of a resource or a competitor, a modi cation species can cause strong effects on a pair-wise interaction, consequently leading to strong effects at population, community, and ecosystem levels (5,7,35). Theoretical and empirical studies found that HOIs increase the robustness of food webs (4,(11)(12)(13), and the structure of two interactive HOIs can stabilize biodiversity-rich ecological networks (11). With such a recognition, however, most theoretical and empirical HOIs studies are limited to answer how a pairwise interaction is affected by a third species (5,14,36).…”
Section: Discussionmentioning
confidence: 99%
“…interaction modi cation, in contrast to interaction chain, (2)), has been widely recognized in ecological studies (3)(4)(5)(6)(7)(8)(9)(10). Yet, studies remain in theoretical explorations of large communities focusing on diversity and stability (4,(11)(12)(13), or consumption coe cients in small or large ecological communities with only one degree HOIs (i.e. one additional species modifying one pair-wise interaction) (5,7,8,10,14,15).…”
Section: Introductionmentioning
confidence: 99%
“…Amongst the non-trophic interactions, higher-order interactions (HOIs) or interaction modifications (the modulation of a pairwise interaction by a third species) (Wootton 1993), play a particularly important role in stabilising species coexistence (Hammill et al 2015;Kelsic et al 2015;Bairey et al 2016;Grilli et al 2017;Terry et al 2019;Singh & Baruah 2021). For instance, they can attenuate negative interactions, such as when non-prey species increase the persistence of predation-susceptible species by modifying the ability of predators to detect prey (Hammill et al 2015).…”
Section: Introductionmentioning
confidence: 99%